2004
DOI: 10.1007/s00441-004-0875-9
|View full text |Cite
|
Sign up to set email alerts
|

Acidophilic granulocytes of the marine fish gilthead seabream ( Sparus aurata L.) produce interleukin-1� following infection with Vibrio anguillarum

Abstract: The fish immune response to Gram-negative bacteria is poorly understood. In this study, we use a monoclonal antibody (mAb) specific to acidophilic granulocytes from the marine fish gilthead seabream (Sparus aurata L.), together with an antiserum specific to interleukin-1beta (IL-1beta) from this species, in order to investigate whether these cells are involved in the immune response against the pathogenic bacterium Vibrio anguillarum and, in particular, in the production of the pro-inflammatory cytokine IL-1be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…The data presented in this study strongly suggest that mobile sbNLCs are also able to specifically home a tissue, i.e., the testis, in response to a physiological need. Moreover, such behavior on the part of sbNLCs might be extended to other tissues, as the peritoneal exudate of noninfected fish contains ϳ20% of resident sbNLCs [12]. In mammals, it has been reported that the uterine cycle involves the recruitment and infiltration of large numbers of circulating eosinophils at estrus [21] and that cytokines are involved in such a process [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data presented in this study strongly suggest that mobile sbNLCs are also able to specifically home a tissue, i.e., the testis, in response to a physiological need. Moreover, such behavior on the part of sbNLCs might be extended to other tissues, as the peritoneal exudate of noninfected fish contains ϳ20% of resident sbNLCs [12]. In mammals, it has been reported that the uterine cycle involves the recruitment and infiltration of large numbers of circulating eosinophils at estrus [21] and that cytokines are involved in such a process [22].…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that the activities of sbNLCs are modified by the microenvironment of the testis. In fact, testicular sbNLCs are able to constitutively produce IL-1␤ [8], whereas head-kidney, peripheral blood, and peritoneal exudate sbNLCs only produce IL-1␤ upon activation [12]. Furthermore, the phagocytic activities of head-kidney sbNLC are modulated by testicular soluble factors or cells, suggesting the functional plasticity of sbNLCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these cell types, acidophilic granulocytes have been suggested to be the equivalent of mammalian neutrophils, being the predominant cell type involved in the immune response against bacterial or viral pathogens in GSB (Couso et al 2001;Chaves-Pozo et al 2004Dezfuli et al 2012b). Mast cells, showing functional and morphological similarities to mammalian mast cells, play a role in the mucosal immune response of GSB and other teleosts (Reite and Evensen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand flow cytometry techniques and electron microscopy combined with methanol fixed blood smears and paraffin embedded tissue subjected to immunofluorescence and peroxidase-antiperoxidase methods using an anti-Il1 and G7 immunostaining analysis revealed that the acidophilic granulocytes in the gilthead seabream are the first cell type to response to an infection mobilizing to the site of infection, phagocyting the pathogen and re-circulating to the head-kidney and spleen to act as antigen presenting cells (Chaves-Pozo et al, 2004a, 2005c. Interestingly, blood circulating acidophilic granulocytes only contained Il1 upon infection, however testicular acidophilic granulocytes constitutively produced Il1 , 2004a. Moreover, in the testis some spermatogonia, spermatocytes and scattered interstitial cells also produced Il1 (Chaves-Pozo et al, 2008a).…”
Section: Characterization Of Immune Cells and Molecules In The Gonadsmentioning
confidence: 99%